THE INFLUENCE OF ORGANIZATIONAL CLIMATE AND WORK-LIFE BALANCE ON DRIVER LOYALTY AT PT. TRANS ANTAR NUSABIRD - Angga Pratama; Ninik Anggraini; Guruh Dwi Pratama (International Journal Management and Economic, 2025)
This study examines the influence of organizational climate and work-life balance on driver loyalty at PT. Trans Antar Nusabird, South Jakarta. Using a quantitative approach, data were collected from 312 drivers through questionnaires with a Likert scale. Organizational climate was measured through leadership style, communication, and support systems, while work-life balance was assessed by time management, role balance, and personal life satisfaction. Driver loyalty was evaluated based on compliance, responsibility, and integrity. The results reveal that organizational climate significantly influences driver loyalty, with a positive regression coefficient of 0.406 and a significance value of 0.000. Conversely, work-life balance does not show a significant impact on driver loyalty, as indicated by a regression coefficient of 0.078 and a significance value of 0.243. Simultaneously, organizational climate and work-life balance have a combined positive effect on driver loyalty, accounting for 47.5% of the variance, with a significance value of 0.000. The study concludes that a positive organizational climate is a key determinant of driver loyalty, while work-life balance requires further exploration. PT. Trans Antar Nusabird is recommended to enhance its organizational climate through leadership and communication improvements, as well as explore better work-life balance initiatives